(untitled) - Khalidi, Tarif (Cambridge [England], 1994)
Tarif Khalidi examines how Arabic-Islamic culture of the pre-modern period viewed the past, how it recorded it, and how it sought to answer the many complex questions associated with the discipline of history. The author combines a chronological with a topical approach to place the tradition within its wider intellectual context and socio-political environment, while quotations from historians across the period introduce the English-speaking reader to some of the principal intellectual texts of Arabic Islamic culture.
Keywords: Islamic Empire,Historiography,Đế chế Hồi giáo; Historiography,Islamic Empire,Sử ký